1994
DOI: 10.1029/94jd00225
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of surface albedo from space: A parameterization for global application

Abstract: This study proposes a simple parameterization to derive surface broadband albedo from satellite observations, using the results of detailed radiative transfer computations for a variety of atmospheric and surface conditions. The end result is a single equation that directly yields surface albedo from observed albedo at the top of the atmosphere, solar zenith angle, and total precipitable water. It was demonstrated that the parameterization is valid for retrieval of both instantaneous and daily mean surface alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(84 citation statements)
references
References 65 publications
1
83
0
Order By: Relevance
“…For surface albedo changes, the linear relationship with planetary albedo changes, Eq. (4), is supported by the results of radiative transfer models (Chen and Ohring, 1984;Li and Garand, 1994). Under a clear-sky, f a represents the mean effective "two-way" transmittance of the atmosphere:…”
Section: Shortwave Optionsmentioning
confidence: 84%
“…For surface albedo changes, the linear relationship with planetary albedo changes, Eq. (4), is supported by the results of radiative transfer models (Chen and Ohring, 1984;Li and Garand, 1994). Under a clear-sky, f a represents the mean effective "two-way" transmittance of the atmosphere:…”
Section: Shortwave Optionsmentioning
confidence: 84%
“…Li and Garand (1994) observed that aerosol effects on surface albedo retrievals are smallest when surface albedo is near 0.5, which is approximately the albedo of the brightest regions of Sahara. Considering also that the AVHRR solar channel radiances used for CLARA-A1-SAL have been recalibrated using the MODIS radiance record, we can explain why MOD43C3 and CLARA-A1-SAL agree very well over high-reflectance deserts; differences in atmospheric correction inputs have minimal effect, and the underlying radiance data records are linked.…”
Section: Comparison Of the Dataset With Mcd43c3 Productsmentioning
confidence: 98%
“…Equations (2)-(4) are adopted from Li and Garand (1994). Note that the diurnal variation of SW CRF not only includes the effect of varying SZA, but also the diurnal changes in DCCs.…”
Section: H Yan Et Al: Long-term Aerosol-mediated Changes In Cloud Rmentioning
confidence: 99%